Vpis družbenika v sodni register tudi po uveljavitvi novele ZGD-1I nima oblikovalnih učinkov za pridobitev poslovnega deleža - Plavšak, Nina (Podjetje in delo, 2016)
The author substantiates that despite the implementation of the ZGD-1I Act Amending the Companies Act, amending paragraph 1 of Article 482 the Company Act, the entry of the transfer of shareholding in a limited liability company is not a prerequisite for this transfer to become legally effective (i.e. that the entry of the transfer in the register does not have constitutive effects) and that this amendment has no effect on specific rules of Article 199 of insolvency law.
Keywords: gospodarske družbe; gospodarsko pravo; sodni register